2015
DOI: 10.1186/s12989-016-0156-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biodistribution and physiologically based pharmacokinetic modeling of inhaled fresh and aged cerium oxide nanoparticles in rats

Abstract: BackgroundCerium oxide (CeO2) nanoparticles used as a diesel fuel additive can be emitted into the ambient air leading to human inhalation. Although biological studies have shown CeO2 nanoparticles can cause adverse health effects, the extent of the biodistribution of CeO2 nanoparticles through inhalation has not been well characterized. Furthermore, freshly emitted CeO2 nanoparticles can undergo an aging process by interaction with other ambient airborne pollutants that may influence the biodistribution after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 57 publications
(102 reference statements)
0
65
0
Order By: Relevance
“…instillation of CeO 2 NPs. The DNA damage, inflammation, and oxidative stress observed in the brain could at least partly result from the translocation [18, 56] and, hence, the direct effect of these nanoparticles on the brain. Although the mechanism related to nanoparticle translocation into the brain following pulmonary exposure is not fully understood, it has been shown that nanoparticles can reach the central nervous system using sensory nerves present in the upper respiratory tract and tracheobronchial region and some in the alveolar region [57].…”
Section: Discussionmentioning
confidence: 99%
“…instillation of CeO 2 NPs. The DNA damage, inflammation, and oxidative stress observed in the brain could at least partly result from the translocation [18, 56] and, hence, the direct effect of these nanoparticles on the brain. Although the mechanism related to nanoparticle translocation into the brain following pulmonary exposure is not fully understood, it has been shown that nanoparticles can reach the central nervous system using sensory nerves present in the upper respiratory tract and tracheobronchial region and some in the alveolar region [57].…”
Section: Discussionmentioning
confidence: 99%
“…In a second attempt, calibrations were performed by adjusting the route-specific parameters only and keeping all other model parameters from the 5 and 30 nm calibrations. With the second approach, the calibration was still unsuccessful for data set 1 from Li et al 49 In spite of differences in size and coatings, the time courses of the ratios after IV administration differed distinctly from the ratios for other exposure routes, illustrated, for example, by the clearly lower blood:liver concentration ratios and the apparently higher spleen:liver concentration ratios ( Figures S13-S15). Noticeably and expected, the concentration in brain was substantially lower than in liver after IV administration (3-5 orders of magnitude) and IT instillation (2-4 orders of magnitude) compared to inhalation exposure (0-2 order of magnitude), suggesting uptake via olfactory nerves ( Figure S15).…”
Section: Inhalation It Instillation and Oral Exposurementioning
confidence: 98%
“…15,[60][61][62][63][64][65][66] Inhalation or IT instillation were addressed in seven publications, which included 14 data sets. 13,14,18,49,53,67,68 Oral uptake was described in six publications, which included 12 data sets. 14,17,53,67,69,70 The experimental studies are summarized in Tables 1-4. Due to the limited and scattered nature of these biodistribution studies, assigning the data to calibration and validation sets could not be randomized.…”
Section: Data Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…In vitro rate constant structure First-order rate constants are variables that describe a proportion (fraction) of drug entering or leaving a specific compartment at any point in time (units of time −1 ). For purposes of this study, in vitro rate constants were scaled according to methods used by Li et al (8,64), where a total maximum first-order uptake rate (hour −1 ) is optimized to animal datasets according to a general equation…”
Section: Cell Space Compartmentmentioning
confidence: 99%